Compiled in commemoration of the decennial of the Bank of Chosen (Seoul, 1919)
In compiling his album our first endeavour was to procure good pictures with enough variety in them to represent every phase of social and economic progress, and the text, to link together these pictures with words, so that pictures and words would help each other in giving as true an idea as possible about the countries concerned.